The molecular basis of odor coding in the Drosophila antenna. - Hallem, E.A.; Ho, M.G.; Carlson, J.R. (Cell, 2004)
We have undertaken a functional analysis of the odorant receptor repertoire in the Drosophila antenna. Each receptor was expressed in a mutant olfactory receptor neuron (ORN) used as a "decoder," and the odor response spectrum conferred by the receptor was determined in vivo by electrophysiological recordings. The spectra of these receptors were then matched to those of defined ORNs to establish a receptor-to-neuron map. In addition to the odor response spectrum, the receptors dictate the signaling mode, i.e., excitation or inhibition, and the response dynamics of the neuron. An individual receptor can mediate both excitatory and inhibitory responses to different odorants in the same cell, suggesting a model of odorant receptor transduction. Receptors vary widely in their breadth of tuning, and odorants vary widely in the number of receptors they activate. Together, these properties provide a molecular basis for odor coding by the receptor repertoire of an olfactory organ.